G8 high school reform results in higher grade repetition rates and lower graduate age, but does not affect graduation rates - Mathias Huebener; Jan Marcus (DIW Economic Bulletin, 2015)
The G8 high school reform to reduce the total number of years spent at Gymnasium (Germany's academic-track secondary school) has been more controversial than almost any other education reform in recent years. Although there are few reliable empirical findings on the effects of the G8 reform, several federal states are already considering a return to the old system, which required 13 years - rather than 12 under the G8 system - for graduation from Gymnasium. A new study by DIW Berlin examines the different effects of the G8 reform using administrative data on all students who graduated from Gymnasium between 2002 and 2013. The study shows, among other things, that the G8 reform has reduced the age of graduation from Gymnasium by an average of ten months - and not the twelve months Gymnasium schooling was reduced by. One reason for this is that the share of students who repeated a grade during their time at Gymnasium rose by three percentage points - approximately a fifth - as a result of the reform. The sharpest rise in grade repetitions was seen in the final years (Oberstufe), with boys being more strongly affected on average than girls. The share of students who graduated from Gymnasium (thereby earning their university entrance qualification or Abitur), however, was unaffected by the G8 high school reform.
Keywords: I28; J18; D04; 330; G12; G8 high school reform; graduation age; grade repetition; grade retention; graduation rates; learning intensity; instructional time